Evaluating Research for Development: Innovation to Navigate Complexity - Apgar, Marina; Snijder, Mieke; Higdon, Grace Lyn; Szabo, Sylvia (The European Journal of Development Research, 2023)
Large publicly funded programmes of research continue to receive incre ased investment as interventions aiming to produce impact for the worl d’s poorest and most marginalized populations. At this intersection of research and development, research is expected to contribute to compl ex processes of societal change. Embracing a co-produced view of impac t as emerging along uncertain causal pathways often without predefined outcomes calls for innovation in the use of complexity-aware approach es to evaluation. The papers in this special issue present rich experi ences of authors working across sectors and geographies, employing met hodological innovation and navigating power as they reconcile tensions . They illustrate the challenges with (i) evaluating performance to me et accountability demands while fostering learning for adaptation; (ii ) evaluating prospective theories of change while capturing emergent c hange; (iii) evaluating internal relational dimensions while measuring external development outcomes; (iv) evaluating across scales: from me asuring local level end impact to understanding contributions to syste ms level change. Taken as a whole, the issue illustrates how the resea rch for development evaluation field is maturing through the experienc es of a growing and diverse group of researchers and evaluators as the y shift from using narrow accountability instruments to appreciating e mergent causal pathways within research for development.